Immune checkpoint inhibitor-associated pituitary adverse events: an observational, retrospective, disproportionality study - Bai, X.; Chen, X.; Wu, X.; Huang, Y.; Zhuang, Y.; Chen, Y.; Feng, C.; Lin, Xiahong (Journal of endocrinological investigation, 2020)
Purpose The aim of this study was to identify and characterize immune checkpoint inhibitors (ICIs)-associated pituitary adverse events (AEs). Methods This is a retrospective disproportionality study based on VigiBase, the World Health Organization (WHO) global database of individual case safety reports (ICSRs), with a study period from January 1, 2011 to March 6, 2019. Information component (IC) and reporting odds ratio (ROR) are measures of disproportionate analysis. IC was used to evaluate the association between ICIs and pituitary AEs, while ROR was used to evaluate the differences in reporting of pituitary AEs between different ICI subgroups. Results The following ICI-associated pituitary diseases have been increasingly reported: hypophysitis (835 reports; information component 6.74 [95% CI 6.63–6.83]), hypopituitarism (268; 6.12 [95% CI 5.92–6.27]), pituitary enlargement (28; 5.19 [95% CI 4.57–5.63]). The anti-CTLA-4 subgroup had a stronger association with hypophysitis/hypopituitarism than the anti-PD (anti-PD-1 or anti-PD-L1) subgroup (ROR 8.0 [95% CI 6.7–9.6]). Among ICI-associated hypophysitis/hypopituitarism cases, the proportion of male was higher than female (630 [63.9%] vs 356 [36.1%]). Anti-CTLA-4 subgroup and ICI combination (nivolumab plus ipilimumab) subgroup both had a significantly earlier onset time than anti-PD subgroup (67 days [IQR 48–87]; 90 [IQR 34–155]; 140 [IQR 62–218], both p < 0.05). Other endocrinopathies that co-occurred with hypophysitis/hypopituitarism were adrenal insufficiency, thyroid dysfunction, diabetes mellitus and diabetes insipidus. Gastrointestinal disorder was the most common concurrent disease except for endocrinopathies. Conclusions ICI-associated pituitary adverse events have significantly increased, and their clinical characteristics should be kept in mind by oncologists and endocrinologists who manage patients treated by immunotherapy.